1970
DOI: 10.1515/zna-1970-0509
|View full text |Cite
|
Sign up to set email alerts
|

Field-dependent Mechanism of Anomalous Proton Conductivity and the Polarizability of Hydrogen Bonds with Tunneling Protons

Abstract: The displacement of the excess charge of the proton in acid solutions is caused by a structure migration of groupings H5O2+ or H9O4+ . The processes which take place during structure migration are discussed on the basis of results gained in IR-investigations. In an electrical field the structure migration is given a preferred direction. The hydrogen bond with the tunneling proton in H5O2+ and the grouping H3O+ in H5O2+ become polarized. Comparison of both polarizabilities demonstrates that, contrary to previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2

Year Published

1978
1978
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(30 citation statements)
references
References 0 publications
3
25
2
Order By: Relevance
“…Contribution of the π‐conjugated phenyl moieties of the peptide to the observed polarizability was found to be small by the significantly lower signal of Aβ‐Q. Indeed, it was reported that proton polarizability through hydrogen bonds network is two orders of magnitude higher than electron polarizability . Hence, we assign the EFM signal to mobile proton charges in the peptide fibrils.…”
Section: Resultsmentioning
confidence: 75%
“…Contribution of the π‐conjugated phenyl moieties of the peptide to the observed polarizability was found to be small by the significantly lower signal of Aβ‐Q. Indeed, it was reported that proton polarizability through hydrogen bonds network is two orders of magnitude higher than electron polarizability . Hence, we assign the EFM signal to mobile proton charges in the peptide fibrils.…”
Section: Resultsmentioning
confidence: 75%
“…The aim of the present article is to show that trigonometric DWP provides the expressions for the energy levels and their corresponding wave functions for HB in CrOOH and KH 2 PO 4 along with their polarizability. The tunneling process for a proton is known to yield a dominant contribution to the extremely high polarizability of HB [22], [23], [24], [25], [26]. This problem was thoroughly investigated by Zundel and co-authors (see [22], [25], [26] and refs.…”
Section: Introductionmentioning
confidence: 99%
“…These proton polarizabilities arise because of shifts of the protons within these hydrogen bonds. All of these results were obtained by theoretical treatments (Weidemann and Zundel, 1970;Janoschek et al, 1973;Zundel, 1976;Eckert and Zundel, 1987; Borgis et al, 1992; Zundel and Eckert, 1989) based on and proven by a very large number of infrared (Zundel (1976), Zundel (1992a), and references therein) and Raman Danninger and Zundel (1980) studies. These proton polarizabilities are particularly large in the case of hydrogen-bonded chains because in such chains a collective proton-tunneling occurs (Zundel, 1976;Eckert and Zundel, 1988a, b;Zundel, 1992b;Zundel and Brzezinski, 1992).…”
Section: Introductionmentioning
confidence: 88%